A structural equation modeling of perceived justice in Malaysian telecommunication sector - Kumar Piaralal, Shishi; Piaralal, Niriender Kumar; Bhatti, Muhammad Awais (Canadian Center of Science and Education, 2015)
Perceived justice is one of important factor in previous studies of service recovery that influences satisfaction of service recovery.It can be assessed in two method namely uni or multi-dimensional.The objective of this research is to examine perceived justice measurement as uni or multi-dimensional towards mobile phone users in the telecommunications industry.Data analysis technique used was Structural Equation Model (SEM).The multi-dimensional nature of justice and satisfaction was verified based on confirmatory factor analysis.The measurement model of the hypothesized model confirmed the non multicollinearity results among the variables. The findings show that the perceived justice measurement fits the data better in terms of multi-dimensional. The limitations of this studied noted and further research suggestions are also included.